1982
DOI: 10.1121/1.387985
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic streaming in superfluid helium

Abstract: Quantitative measurements of acoustic streaming velocity in liquid helium as a function of sound intensity {up to the cavitation threshold}, frequency {1, 3, and 10 MHz}, and temperature {1.43 K

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

1985
1985
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Here appears one of the greatest paradox of acoustic streaming: although the momentum source for the fluid is proportional to the viscosity, it mostly dissipates this momentum through shear stress, such that streaming velocity is expected to be independent of viscosity. Experimentally, it has been confirmed that acoustic streaming occurs for a wide range of fluids from superfluid Helium (Rooney et al (1982)) to very viscous polymers (Mitome (1998)). Nevertheless, this assertion must be mitigated for two reasons: (i) at large sound intensity or low viscosity (Lighthill (1978)), hydrodynamic momentum convection becomes the main dissipation mechanism resulting in a velocity slope break marking the transition between slow and fast acoustic streaming (Liebermann (1949); Kamakura et al (1995)) (ii) at high viscosity or high frequency, the sound wave attenuates quickly confining the forcing term to a smaller region of space (Nyborg (1953)), which has recently been experimentally evidenced (Dentry et al (2014)).…”
Section: Introductionmentioning
confidence: 91%
“…Here appears one of the greatest paradox of acoustic streaming: although the momentum source for the fluid is proportional to the viscosity, it mostly dissipates this momentum through shear stress, such that streaming velocity is expected to be independent of viscosity. Experimentally, it has been confirmed that acoustic streaming occurs for a wide range of fluids from superfluid Helium (Rooney et al (1982)) to very viscous polymers (Mitome (1998)). Nevertheless, this assertion must be mitigated for two reasons: (i) at large sound intensity or low viscosity (Lighthill (1978)), hydrodynamic momentum convection becomes the main dissipation mechanism resulting in a velocity slope break marking the transition between slow and fast acoustic streaming (Liebermann (1949); Kamakura et al (1995)) (ii) at high viscosity or high frequency, the sound wave attenuates quickly confining the forcing term to a smaller region of space (Nyborg (1953)), which has recently been experimentally evidenced (Dentry et al (2014)).…”
Section: Introductionmentioning
confidence: 91%
“…On the other hand, the present experimental amplitudes are larger than those used to generate vorticity in helium from streaming. 26,27 However, the acoustic absorption (which gives rise to streaming) is very small in the present experiment compared to the absorption in the experiments cited above, which were performed at temperatures above 1 K. Also, the present experiment used pulsed sound (rather than cw) which greatly lowers the resulting streaming velocity. As already noted, the results given here showed no sensitivity to pulse width or repetition rate, which indicates that streaming is not important.…”
mentioning
confidence: 77%
“…Acoustic streaming is a truly ubiquitous phenomenon observed not only in Newtonian fluids, but also in superfluid helium [13] and non-Newtonian viscoelastic liquids [14]. It is used in many different applications: thermoacoustic engines [15], enhancement of electrodedeposition [16], mixing in microfluidics [17,18], enhancement of particle trapping [19,20], micropumping [21], biofouling removal [22], and lysing of vesicles [23].…”
mentioning
confidence: 99%